Pengaruh Integrasi Pencahayaan Alami Pada Sistem Pencahayaan, Terhadap Efisiensi Energi Bangunan Tinggi - Syahrullah, M. Rachmat; Amalia, N.; Khaerunnisa, Khaerunnisa (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
Increasing natural light illumination can reduce lighting energy but has the potential to increase ventilation energy due to higher heat gains in buildings. This condition presents a research problem to determine the optimal compromise for integrating natural light in lighting systems to achieve energy efficiency by examining the impact of building envelopes. The simulation object is a hypothetical, multi-story, air-conditioned office building with a typical floor area of 1600 m², measuring 40m x 40m. The WWR variable is set within a range of 10% - 70%, and the VT variable ranges from 0.1 to 0.9, with an orientation of 0º to the north. The simulation utilizes EnergyPlus v7.0 software, OpenStudio v7.0 plugins, LBNL Window 6.3, and Dialux 10.0. The research results show that integrating natural lighting can reduce lighting energy consumption by up to 66%, ventilation energy by up to 6%, and total energy by up to 20%. The combination of WWR and VT affects energy reduction. Smaller WWRs require low VT glass, medium WWRs require medium VT glass, and larger WWRs require high VT glass. The best energy performance is achieved with medium WWR and medium VT, specifically with a WWR configuration of 50% and glass VT of 0.5. The east and west sides have the highest levels of natural light illumination but also the highest heat gains, while the north and south sides effectively utilize natural lighting with large WWRs. A floor plan ratio of 3:1 is optimal for lighting energy performance, while a 1:2 ratio is best for total energy performance in comparable configurations. Shading components improve energy efficiency by up to 2% for lightshelf types and 4% for overhang types. The level of energy efficiency is also determined by the mechanical systems selected for lighting control, light, and AC types